THE ROLE OF SPRIRITUALITY AND WORK ETHIC IN IMPROVING WORK EFFECTIVENESS IN THE LOGISTICS INDUSTRY - Kusnadi Kusnadi; Budi Prijono (Universitas Padjadjaran, 2023)
One of the most important elements in any organization is people. With competent human resources, an organization can operate effectively and efficiently. This study aims to measure the role of spirituality and work ethic in improving work effectiveness in the logistics industry. The research method uses quantitative which is descriptive and verifiable. The sample determination technique used is probability sampling type propotional stratified random sampling. The employees sampled were 54 people, out of a population of 117 people. Overall, the results of this study show that the staff in this study have spirituality, good work ethic, and high organizational equity and are good in their work. The results showed that the spiritual variable (X1) had a direct effect of 20.20%, which had an indirect effect of 10.60% through its relationship with work ethic (X2), so that the total effect was 30.80%. The work ethic variable (X2) has a direct effect of 12.70%, an indirect effect of 10.60% through its relationship with spirituality (X1), so that the total effect is 23.30%. Thus, the total effect of spirituality (X1) and work ethic (X2) is 54.10%. At the same time, other unexplored factors affecting the efficiency of work in logistics in Jakarta show the value of Pyε = 0.459 or 45.90%. Based on the results of the research, the steps that can be taken by management are to make efforts to further improve the quality of work effectiveness through improving the spirituality and work ethic of employees.